How Does Tiktok Help to Improve Netflix’s Business Performances - Tan, Lay Hong; Hazarika, Anurag; Ahmad Tamizi, Nur Farah Alyaa; AHMAD NAZRI, NUR ARNIESYA; MAT FUZI, NUR ATHIRAH; SAXENA, PRANJAL; MOHD AFFANDI, NUR FARHANA (Asia Pacific Journal of Management and Education (APJME), 2024)
With rapid technological improvements, organisations are constantly looking for new ways to improve performance and reach their target audience. TikTok, a popular social media network, especially among young people, offers businesses a unique potential for interaction and brand recognition. This study evaluates TikTok's positive impact by looking at the precise mechanisms via which it helps to corporate growth, such as its impact on brand awareness and consumer engagement. This study also looks into why companies like Netflix prefer to use TikTok as a marketing tool for company success. A survey questionnaire was given to 150 participants in this study.  The statistics demonstrated a direct association between TikTok use and increases in Netflix's business success, brand recognition, and consumer engagement. These data can help TikTok and businesses like Netflix optimise their strategy and leverage on the platform's potential for long-term growth and success.